2018
DOI: 10.7150/ijbs.27746
|View full text |Cite
|
Sign up to set email alerts
|

SIRT3 Activation by Dihydromyricetin Suppresses Chondrocytes Degeneration via Maintaining Mitochondrial Homeostasis

Abstract: Mitochondrial dysfunction is an important contributor to the development of osteoarthritis (OA). Sirtuin 3 (SIRT3) regulates diverse mitochondrial proteins to maintain mitochondrial homeostasis, and dihydromyricetin (DHM) is reported as a potential SIRT3 activator. This study aims to explore the relevance of SIRT3 and OA, as well as the therapeutic effects of DHM on mitochondrial homeostasis in TNF-α-treated chondrocytes. The relationship between SIRT3 and OA was confirmed by detecting SIRT3 level in vitro and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 34 publications
(40 reference statements)
1
50
0
Order By: Relevance
“…This conclusion seems to oppose our observations. Thereby, our data, combined with the previous studies (Wang et al 2018a), support Sirt3 having multiple effects on mitochondrial stress and its potential functions depend on different cell types and a cellspecific context. Although our present study presents a new signaling pathway responsible for tongue cancer cell death, additional investigations using animal studies or human samples are needed to validate our concept and help transform basic research findings into clinical application.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This conclusion seems to oppose our observations. Thereby, our data, combined with the previous studies (Wang et al 2018a), support Sirt3 having multiple effects on mitochondrial stress and its potential functions depend on different cell types and a cellspecific context. Although our present study presents a new signaling pathway responsible for tongue cancer cell death, additional investigations using animal studies or human samples are needed to validate our concept and help transform basic research findings into clinical application.…”
Section: Discussionsupporting
confidence: 86%
“…Increased Fis1 expression triggered mitochondrial fission that exacerbated mitochondrial damage, ultimately initiating the mitochondriadependent apoptosis pathway in tongue cancer. Notably, a previous study has found that Sirt3 activation promotes Fis1 upregulation in the development of osteoarthritis (Wang et al 2018a). This conclusion seems to oppose our observations.…”
Section: Discussionmentioning
confidence: 97%
“…Among SIRT3 activators, dihydromyricetin and honokiol were tested in various conditions related to mitochondrial functional impairments. Dihydromyricetin was shown to suppress chondrocyte degeneration in osteoarthritis [63]. Honokiol was reported to activate SIRT3 in a study dedicated to the treatment of intervertebral disc degeneration [64].…”
Section: Activators Of Mitophagymentioning
confidence: 99%
“…Differently from nuclear DNA, the mtDNA lacks damage-repair mechanisms, and the mutations are susceptibility to accumulate. A recent study identified that the onset of aging symptoms would be determined by the ratio of mutant to wild-type mtDNA, with a typical threshold effect [19], and thus the mice with a high mutant ratio of mtDNA exhibit advanced aging phenotypes. Although aging-related mtDNA mutation is regarded as incurable and has to wait for the development of genome editing techniques, the supplement of healthy mitochondria will have great promise to decrease the mutant ratio of mtDNA and then slow down the aging phenotypes.…”
Section: Discussionmentioning
confidence: 99%